Analysis of Public Accounting Firm Services and Audit Quality with Structure Conduct Performance Approach in Indonesia Capital Market - Sofia, Alfira; Nurapandi, R Nelly (Jurnal Riset Akuntansi dan Keuangan, 2018)
Abstract. The business aspect of the audit services may lead to abnormal fee audits. This happens because the supply and demand in audit services are unbalanced resulting in an oligopolistic market, in which the audit engagement is concentrated in several public accounting firms. Such market concentration will lead to the structure conduct performance paradigm because the market structure of an industry will cause behavioral changes especially in the determination of reasonable audit fees and will ultimately affect the quality of audit services itself. This study aims to 1) test and analyze the direct effect of audit service market concentration on audit quality in Indonesia capital market; 2) test and analyze the indirect effect of audit service market concentration on audit quality through positive abnormal audit fee in Indonesian capital market. The research was conducted using a quantitative descriptive method. Research data is in the form of secondary data from capital market in Indonesia. The results show that market concentration has not an effect on the decreased audit quality,but market concentrationhasan effect on increase abnormal fee.Â Keywords: market structure; audit fee; audit qualityÂ Abstrak. Aspek bisnis dari layanan audit dapat menyebabkan audit biaya tidak normal. Hal ini terjadi karena pasokan dan permintaan dalam layanan audit tidak seimbang yang mengakibatkan pasar oligopolistik, di mana keterlibatan audit terkonsentrasi di beberapa kantor akuntan publik. Konsentrasi pasar seperti itu akan mengarah pada struktur melakukan paradigma kinerja karena struktur pasar suatu industri akan menyebabkan perubahan perilaku terutama dalam penentuan biaya audit yang wajar dan pada akhirnya akan mempengaruhi kualitas layanan audit itu sendiri. Penelitian ini bertujuan untuk 1) menguji dan menganalisis pengaruh langsung konsentrasi pasar layanan audit terhadap kualitas audit di pasar modal Indonesia; 2) menguji dan menganalisis pengaruh tidak langsung konsentrasi pasar layanan audit terhadap kualitas audit melalui biaya audit abnormal yang positif di pasar modal Indonesia. Penelitian ini dilakukan dengan menggunakan metode deskriptif kuantitatif. Data penelitian berupa data sekunder dari pasar modal di Indonesia. Hasil penelitian menunjukkan bahwa konsentrasi pasar tidak berpengaruh pada penurunan kualitas audit, tetapi konsentrasi pasar berpengaruh pada peningkatan biaya abnormal.Kata Kunci: struktur pasar; biaya audit; kualitas audit